Performance Test of Coconut Shell Grinding Machine For Pyrolysis Process - Novita, Sri Aulia; Santosa, Santosa; Nofialdi, Nofialdi; Andasuryani, Andasuryani; Fudholi, Ahmad (Green Engineering Society, 2024)
Coconut shell is a solid waste of biomass from processed coconuts separated from the flesh. Coconut shells can be reprocessed into products of high economic value. Coconut shells can be processed for bio-oil production via high-temperature pyrolysis. In the pyrolysis process, the coconut shell raw materials are reduced in size to facilitate combustion. The aim of this research was to test the performance of the modified coconut shell grinding machine, determine the effect of water content on the milling process, achieve coconut shell sizes of 3, 5, and 10 mm to enhance the pyrolysis process, and analyze the economics of grinding machine engineering. The size reduction process was carried out using a custom-designed coconut shell grinder that was altered in its sieve section. The sieve sections had diameters of 10, 5, and 3 mm. The coconut shell to be ground had a moisture content of 8–10%. The grinding machine capacity varies with each size, namely 10 mm, 5 mm, and 3 mm, achieving throughput rates of 14.892 kg/h, 7.214 kg/h, and 2.94 kg/hour, respectively. The resulting yield was notably high, ranging from 95 to 96.780%, and the associated yield loss remained low, between 3.2% and 4.8%. During the material size tests, the working RPM was observed at 630.6 for 10 mm, 711.2 for 5 mm, and 1017.18 for 3 mm, and these RPM variations influence the grinding speed.